The importance of communicativeactivities to develop Intercultural Communicative Competence among 7th and 8th grade students) - Арстангалиева, Г. К. (My University, 2016)
The article considers the examples of communicative activities such as role-playing, discussion, projects held by 7 th and 8 th grade students in an English language lesson. The author concludes that these activities have an effective influence on the development of intercultural communicative competence which is essential tool in foreign language teaching
Keywords: intercultural communicative competence; competence; communicative ability; communicative activities; culture; foreign language teaching.